2020
DOI: 10.1039/d0ob00391c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, radiolabelling and initial biological characterisation of 18F-labelled xanthine derivatives for PET imaging of Eph receptors

Abstract: Two new fluorine-18-labelled xanthine derivatives with high binding affinity were synthesised as PET-radioligand candidates for Eph receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Alternatively, in a recent publication, Affinito et al introduced a RNA aptamer targeting EphA2 receptors at human glioblastoma cells for therapeutic purpose-s [ 39 ]. In another recent study, Pretze et al reported two novel xanthine derivatives as potential tracers for imaging of EphA2 and EphB4 overexpressing human A375 melanoma cells [ 40 ]. Although the suitability of those probes still needs to be evaluated in clinical trials, these studies globally underscore the potency of EphB4 as a target for tumor imaging…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, in a recent publication, Affinito et al introduced a RNA aptamer targeting EphA2 receptors at human glioblastoma cells for therapeutic purpose-s [ 39 ]. In another recent study, Pretze et al reported two novel xanthine derivatives as potential tracers for imaging of EphA2 and EphB4 overexpressing human A375 melanoma cells [ 40 ]. Although the suitability of those probes still needs to be evaluated in clinical trials, these studies globally underscore the potency of EphB4 as a target for tumor imaging…”
Section: Discussionmentioning
confidence: 99%
“…Other EphR targeting peptides, including SWL and SNEW, have been radiolabeled ( Table S1 ) [ 351 , 361 ]. Finally, the recently developed [ 18 F]-labeled xanthine derivatives have potential for PET imaging of Eph receptors but lack studies in GB to date [ 362 ].…”
Section: Receptor Tyrosine Kinase Inhibitors (Rtkis) For Gb Therapymentioning
confidence: 99%
“…A third 18 F-radiolabeling approach using xanthine derivatives was published in 2020. 27 Lafleur et al published the lead compound 18 (compound 66 of the citation, IC 50 = 2.3 (EphA2), 1.6 (EphB4)) in 2009. 26 Again, the question of the best labeling position to introduce fluorine-18 was solved by performing docking studies with the EphA3 receptor, representing the similar ATP-binding pocket as EphB4, using crystal structure data and possible fluorine-containing molecules.…”
Section: Eph/ephrin System As a Diagnostic Target In Cancermentioning
confidence: 99%
“… 26 Again, the question of the best labeling position to introduce fluorine-18 was solved by performing docking studies with the EphA3 receptor, representing the similar ATP-binding pocket as EphB4, using crystal structure data and possible fluorine-containing molecules. 27 Based on this result, the two fluorine-containing reference compounds 21a,b were synthesized from 19a,b using Deoxofluor. With this procedure, only the aliphatic OH group of 19a,b is displaced by fluoride under mild conditions ( Scheme 6 ).…”
Section: Eph/ephrin System As a Diagnostic Target In Cancermentioning
confidence: 99%
See 1 more Smart Citation